Physicochemical parameters and coliform content of a compost obtained from organic waste from Camal Frigorífico Riobamba - Jara Arguello, Margarita del Rocio (2016)
Obtaining compost from organic waste is a  viable alternative for the environment, but are high volumes of waste generated without avail the many benefits offered. The objective of this research was the physiochemical determination and coliform content of compost derived from organic waste from municipal slaughterhouse in the city of Riobamba. a completely randomized design with two treatments, T1 consisting of a mixture of dried manure, rumen contents and blood in the ratio 50:25:25 and addition of bacterial broth and T2 with the same proportion but bacterial broth was used. The pH and temperature versus time was determined during aerobic bacteriological digestion. A solid compost Bio-sol was obtained and physico-chemical and microbiological parameters were determined. The results indicated that both treatments reached a maximum temperature of 70 °C. Bacteria treatment with the maximum was reached after seven days while no bacteria at 15 days. The typical succession of the different stages was better defined for treatment without bacteria. Among the treatments, there was a difference of 15 days to achieve stabilization of pH. The chemical composition was similar for both treatments and suitable for organic fertilizers